Funciones ejecutivas y educacion; Comprendiendo habilidades clave para el aprendizaje (Ediciones UC, 2017)
The study of executive functions, a concept born from neuroscience, has grown exponentially in the last 20 years. This growth allows us to identify and understand key components involved in complex behaviors such as learning. For example, the importance of attention, working memory, inhibitory control, among other components. All this considering boys and girls with typical development, but also atypical, which makes it possible to advance in the inclusion and diversity existing in the classroom. The dialogue between Education, Psychology and Medicine begins to have fluidity, allowing progress in clarity not only in its understanding, but also in the effect that its stimulation has both in the field of socio-emotional and academic skills. This book develops the concept of executive functions and provides evidence of its direct relationship with Education, considering contributions from different disciplines. At the same time, it presents an updated synthesis of the neurological bases that support the construct, evidence of its transfer to academic skills, and experiences inside and outside the classroom of its stimulation and evaluation. This is a book that can be of great help to professionals who work with children and young people.